Clinical Outcomes for Stereotactic Ablative Radiotherapy in Oligometastatic and Oligoprogressive Gynecological Malignancies. Issue 2 (1st February 2017) - Mesko, Shane; Sandler, Kiri; Cohen, Joshua; Konecny, Gottfried; Steinberg, Michael; Kamrava, Mitchell
Abstract : Objectives: We report single-institution clinical outcomes of women treated with stereotactic ablative radiotherapy (SABR) for oligometastatic or progressive gynecological malignancies. Materials and Methods: From 2009 to 2015, 47 lesions from 28 patients were treated with SABR and retrospectively analyzed. All patients had oligometastatic (93%) or oligoprogressive (7%) disease. Primary cancer diagnoses were 15 ovarian, 8 endometrial, 2 cervical, 2 vaginal, and 1 uterine carcinosarcoma. Treatment was delivered using a median of 5 fractions to a median total dose of 40 Gy. Targets were grouped by treatment site and assessed for response using Response Evaluation Criteria in Solid Tumors v1.1. Mean biologically effective dose and pre-SABR tumor size were compared with response. Progression-free survival (PFS) was determined using Kaplan-Meier analysis, and toxicity outcomes were graded using Common Terminology Criteria for Adverse Events version 4.03. Results: Median follow-up was 12.8 months. Target locations were 17% liver, 21% lung, 17% paraaortic node, 26% other node, and 19% pelvic soft tissue. After treatment, 34% of targets were stable (SD), 32% had a partial response (PR), 17% had a complete response (CR), and 17% had progressive disease (PD). No failures occurred in lung or nodal targets. Mean ± standard deviation pre-SABR tumor diameter was 24 ± 22 mm. There was a significant difference in mean size between lesions that had a favorable (SD, PR, and CR) versus unfavorable response (PD) (17.2 vs 57.6 mm, P = 0.0044). Lesions that responded favorably were also more likely to have received a higher biologically effective dose (79.0 vs 59.6 Gy, P = 0.027). Median PFS was 10.8 months, and 1 patient experienced grade 3 toxicity. Conclusions: The SABR is a safe and effective local treatment modality in patients with oligometastatic gynecological disease. Distant progression remains the primary mode of failure in this patient population. In carefully selected patients, a combination of systemic treatment and SABR may offer long-term PFS.